IMPLEMENTASI KONSEP GREEN HOSPITAL PADA RUMAHSAKIT PANTI NUGROHO YOGYAKARTA - , ZAMAKHSYARI FARID A; , Dr.Eng.Suharyanto, ST, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Attempts to create a green building growing up is given to the increase in global warming and that there are also environmental factors are increasingly disrupted by large-scale exploitation of energy, and the limited energy resources available and the bad impact effect of energy consumption on the environment. This study aims to help overcome these problems through a new concept applied Green Hospital in Yogyakata Panti Nugroho regarding some coverage areas, but in this study the concept focussed to the electrical and electrical energy. The results of research, that is the context of hospital efficiency green electricity and energy consumption conditions at this hospital very well, and meet the criteria for green hospital. Lighting conditions there are some spaces that have not been standardized, seen from the quality of the measurement. In the system of air at room temperature and humidity conditions there are a few rooms that still does not meet the standards set in the department of health, and SNI. With the implementation Green Hospital, obtained retrofitting electrical systems, lighting and electric systems in accordance with the concept of green hospital. Conditions that are environmentally friendly, efficient in energy consumption, as well as convenient in hospital quality.